Phoenix rising: legal reforms and changes in valuations in Finland during the economic crisis - Timo Korkeamäki; Yrjö Koskinen; Tuomas Takalo (Bank of Finland, 2007)
Finland experienced an extremely severe economic depression in the early 1990s.In the midst of this crisis, significant new legislation was passed that increased supervisory powers official market regulators and reformed bankruptcy procedures significantly decreasing the protection of creditors.We show that the introduction of these new laws resulted in positive abnormal stock returns.The new laws also lead to increases in firms'Tobin's q, especially for more levered firms.In contrast to previous studies, our results also suggest that public supervision of financial markets fosters rather than hampers financial market development.
URN:NBN:fi:bof-20140807528
Keywords: G34; K22; 330; corporate governance; bankruptcy; financial supervision; shareholder protection; creditors' rights; corporate valuations; political economy